2012
DOI: 10.1007/s00787-012-0262-0
|View full text |Cite
|
Sign up to set email alerts
|

Processing speed and executive functions predict real-world everyday living skills in adolescents with early-onset schizophrenia

Abstract: Cognition and clinical variables are known to be among the most predictive factors of real-world social functioning and daily living skills in adult-onset schizophrenia. Fewer studies have focused on their impact in adolescents with early-onset schizophrenia (EOS). The aim of this study is to examine the relationships and the predictive value of cognition and clinical variables on real-world daily living skills in a sample of adolescents with EOS. Cognitive, clinical and real-world everyday living skills measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 72 publications
2
13
0
Order By: Relevance
“…39,41,42 Though the link between cognition and functional outcome is complex and mediated by both social and functional competency skills, it has been demonstrated that neurocognitive variables relate to specific functional domains of work/productivity and daily living skills in individuals with schizophrenia. [43][44][45][46] The associations between cognitive and functional outcomes have similarly been demonstrated for several of the cognitive skills that improved and persisted in our sample. For example, cognitive flexibility, 47 executive function, 21,43,46 processing speed 46 and working memory have previously been shown to impact functioning in patients with schizophrenia.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…39,41,42 Though the link between cognition and functional outcome is complex and mediated by both social and functional competency skills, it has been demonstrated that neurocognitive variables relate to specific functional domains of work/productivity and daily living skills in individuals with schizophrenia. [43][44][45][46] The associations between cognitive and functional outcomes have similarly been demonstrated for several of the cognitive skills that improved and persisted in our sample. For example, cognitive flexibility, 47 executive function, 21,43,46 processing speed 46 and working memory have previously been shown to impact functioning in patients with schizophrenia.…”
Section: Discussionsupporting
confidence: 72%
“…The associations between cognitive and functional outcomes have similarly been demonstrated for several of the cognitive skills that improved and persisted in our sample. For example, cognitive flexibility, executive function, processing speedand working memory have previously been shown to impact functioning in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…1 Poor cognitive control is associated with reduced clinical insight, 2 lower levels of remission, 3 reduced daily living skills 4 and greater suicide risk 5 in patients with schizophrenia. Response inhibition, the ability to inhibit planned or ongoing motor actions, represents an important subcomponent of cognitive control.…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to note that executive deficits have important real-world consequences for individuals with schizophrenia. Lower executive skills predict reduced insight (Chan et al, 2012), reduced daily living skills (Puig et al, 2012), and reduced levels of remission (Hofer et al, 2011). Despite these prominent correlates, caution must be exercised in asserting the primary cognitive importance of executive deficits, as general intellectual ability (“g”) correlates substantially with most measures of executive skill.…”
mentioning
confidence: 99%